MENINGKATKAN PEMASARAN BATIK PENATARAN SEBAGAI WUJUD PEMBERDAYAAN PENGRAJIN BATIK PERTAKINA BLITAR - Supriyono; Yusniarsi Primasari; Devita Sulistiana; Hesty Puspita Sari; Nurma Atalsa Sofyansyah; Puspanegara, Damayanti (JANITA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
PERTAKINA (Perkumpulan Tenaga Kerja Purna) is a non-governmental organization established in 2016 in Blitar to support former Indonesian Migrant Workers (PMI) in starting their own businesses. The objectives of this Community Service program are: 1) To empower the community by developing a SIPOC management model for batik and woven fabric entrepreneurship at PERTAKINA, 2) To advance batik and woven fabric artisans through training on the SIPOC management model, 3) To enhance the quality and quantity of batik and woven fabric production at PERTAKINA through the use of the SIPOC management model application, 4) To develop the creative skills of batik and woven fabric making for students of Islamic University of Balitar through their involvement in this Community Service program. The empowerment method involves training and mentoring on the SIPOC management model for batik and woven fabric entrepreneurship. The participants in this program include 20 batik artisans from Penataran under PERTAKINA and 2 students from Islamic University of Balitar. Evaluation results from the Kirkpatrick Four-Level Model show that 100% of participants reacted very positively to the development of the SIPOC management model, 98% rated the training materials, methods, and timing as very good, and the remaining 2% rated them as good. It is recommended that PERTAKINA management and supporting institutions monitor and evaluate the business results at least 4 months after this training.